ANALISIS PENERAPAN SISTEM INSENTIF BERBASIS KINERJA (Studi Kasus pada CV. Trisno Adi–Lombok) - Tama Krisnahadi (SANGKAREANG, 2016)
This study aims to determine the process of implementing performance-based incentive system on CV. Trisno Adi-Lombok, its constraints and issues encountered during the process, seeking alternative solutions to the identified problems, as well as to determine the performance of employees who earn incentives on the CV. Trisno Adi. This study employs explanatory, qualitative and case study methodology. By adopting the triangulate technique, data is collected by pursue of interview, and implementation of Focus Group Discussion (FGD). Over and above, the other supporting data is sufficient to fulfill the requirements. Data analysis indicates that the implementation of performance based insentive system on CV. Trisno Adi has been run in accordance with the provision applicable to the company, although there are problems in implementation. These problems include: the difficulty in setting benchmarks of performance appraisal, the amount of the incentive will be given to employees, the determination of the socialization process obstacles, performance appraisal systems are subjective by their leaders, as well as the distribution process that takes up to one month. Solutions to overcome these problems, among others; supervisior of discussions with each department are, to socialize face to face with a direct link between the management company with employees, implementing a performance appraisal system is hierarchical tiered, and coordinate with related parties play roles in the distribution of incentives. Employee performance incentives generally increased as measured by the Achievement Assesment Index (AAI) of those employees who performed regularly every month and employee performance appraisals at the end of the tobacco season.